Designing E-Commerce Aegle Marmelos with Dropshipping Concept - Erkrista, Vadil Safrilian; Sunarto, M.J. Dewiyani; Lemantara, Julianto (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
Craft and musical instruments made from aegle marmelos are now increasing in demand, from local peoples to foreigners. The large number of enthusiasts causes the demand for craft from aegle marmelos to increase, making aegle marmelos crafters find it difficult to find aegle marmelos raw materials. The difficulty of getting raw materials for aegle marmelos is because aegle marmelos trees are rarely found, this is because the community already considers aegle marmelos as waste so that rarely want to plant aegle marmelos trees. To overcome these problems, the solution that can be given is to create an e-commerce website with the concept of dropshipping. The concept of dropshipping was chosen because researchers as e-commerce owners do not need to stock the aegle marmelos first and without even having to send the aegle marmelos fruit. The results of trials that have been carried out with black box testing are the existence of an e-commerce website with a special concept of dropshipping to sell aegle marmelos that is able to bring together producers and suppliers of aegle marmelos so that it helps crafters obtain information on aegle marmelos for sale and can make purchases of aegle marmelos while suppliers can sell aegle marmelos by confirming stock, withdrawing balances, and obtaining information in the form of a sales report graph.